The Digital Synaptic Neural Substrate A New Approach to Computational Creativity - Iqbal, Azlan; Guid, Matej; Colton, Simon; Krivec, Jana; Azman, Shazril; Haghighi, Boshra (SpringerBriefs in Cognitive Computation, 2016)
This book describes a new computational approach to creativity. With chess as the domain of investigation, the authors show experimentally how a computer can be imbued with the 'spark' of creativity that enables it to compose chess problems or puzzles that are both challenging and aesthetically appealing to humans. This new approach called the Digital Synaptic Neural Substrate (DSNS) mimics the brain's ability to combine fragments of seemingly unrelated information from different domains (such as chess, photographs and music) to inspire itself to create new objects in any of them. Representing the cutting edge in computational creativity research, this book will be useful to students, educators and researchers in the field as well as artificial intelligence (AI) practitioners, in general.